SOCIAL BOND ANALYSIS OF CORRECTIONAL INMATES AT CLASS IIA CIBINONG CORRECTIONAL INSTITUTION: THE PHENOMENON OF VIOLENCE AMONG INMATES - Salma, Rantri Ridho (Universitas Negeri Medan, 2023)
Correctional Institution has the goal of guiding criminals to obtain a better life, be able to reintegrate and be accepted by the society. However, realizing such goal is not as easy. As a place where people from various backgrounds and different criminal records, Correctional Instituion has become an ideal area and prone to disputes. This includes violence among inmates, that is reported to be the most common type of violent in prison. Nonetheless, it is not impossible to avoid such issues in the prison setting. In order to understand this possibility, this article attempt to study the social life in prison in relation to violence among inmates. Mainly, this study aims to: 1) find out the condition of violence among inmates in Cibinong Correctional Institution; and 2) analyze social bond to understand the phenomenon of violence among inmates in Cibinong Correctional Institution. This study uses a qualitative approach to be able to understand the object of study concretely through their own thoughts and words. The findings of this study indicate that there were no cases of violence among inmates in the form of instrumental attacks, include bullying, domination of power among inmates, fights among inmates, or clashes between inmate groups. However, the expressive type of violence, triggered by emotional response of inmates, happened a few times. The results of the analysis show that inmates in Cibinong Correctional Institution have strong social bonds, which can completely prevent inmates from engaging in instrumental violence among inmates. Meanwhile, expressive attacks can be handled.